"Pseudo" hypertrophic neuropathy of childhood. Issue 2 (February 1995) - Baba, M; Takada, H; Miura, H; Okushima, T; Matsunaga, M
Abstract : A 9 year old boy had chronic progressive motor-sensory neuropathy that started in early infancy. He had enlarged nerves and pes cavus deformity. Motor conduction studies showed very dispersed, polyphasic compound muscle action potentials with conduction velocities around 2 m/s. A sural nerve biopsy showed severe loss of myelinated fibres. Two months of treatment with corticosteroids restored muscle power. During this time the enlarged nerves became normal and electrophysiological recovery was achieved. Chronically acquired neuropathy in infancy is strikingly similar to genetically determined neuropathy.